Technical Note: Simulation of dose buildup in proton pencil beams. Issue 8 (30th June 2019) - Kelleter, Laurent; Zhen‐Hong Tham, Benjamin; Saakyan, Ruben; Griffiths, Jennifer; Amos, Richard; Jolly, Simon; Gibson, Adam
Abstract : Purpose: The purpose of this study is to characterize the magnitude and depth of dose buildup in pencil beam scanning proton therapy. Methods: We simulate the integrated depth–dose curve of realistic proton pencil beams in a water phantom using the Geant4 Monte Carlo toolkit. We independently characterize the electronic and protonic components of dose buildup as a function of proton beam energy from 40 to 400 MeV, both with and without an air gap. Results: At clinical energies, electronic buildup over a distance of about 1 mm leads to a dose reduction at depth of the basal layer (0.07 mm) by up to 6% compared to if no buildup effect were present. Protonic buildup reduces the dose to the basal layer by up to 16% and has effects at depths of up to 150 mm. Secondary particles with a mass number A > 1 do not contribute to dose buildup. An air gap of 1 m has no significant effect on protonic buildup but reduces electronic buildup below 1%. Conclusions: Protonic and electronic dose buildup are relevant for accurate dosimetry in proton therapy although a realistic air gap reduces the electronic buildup to levels where it can be safely neglected. We recommend including electrons and secondary protons in Monte Carlo‐based treatment planning systems down to a predicted range of 10–20 μ m in order to accurately model the dose at depths of the basal layer, no matter the size of the air gap between nozzle and patient.